2018
DOI: 10.1177/1535370218774539
|View full text |Cite
|
Sign up to set email alerts
|

Novel interleukin-33 and its soluble ST2 receptor as potential serum biomarkers in parotid gland tumors

Abstract: An increasing number of patients with parotid gland tumors have been observed in recent years. The relationship between the immune system and tumor formation is thoroughly investigated. However, newly discovered molecules offer a new insight into the pathophysiology of malignancies. It would be ideal to find an easily determinable biomarker of tumor existence, its malignant potential or a biomarker suggesting the probability of disease recurrence. Our study is the first to examine serum concentrations of IL-33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Recent studies have also found that soluble ST2 levels were highly expressed in the liver, lung, and breast cancer; malignant glioma; and other tumor tissues; this was associated with the occurrence, invasion, and metastasis of tumors [ 43 45 ]. In the present study, we found that the frequency of the ST2 rs3821204 C allele was higher in the HCC group than in the healthy control group; our results were consistent with the findings of Wei et al on Chinese HCC patients [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also found that soluble ST2 levels were highly expressed in the liver, lung, and breast cancer; malignant glioma; and other tumor tissues; this was associated with the occurrence, invasion, and metastasis of tumors [ 43 45 ]. In the present study, we found that the frequency of the ST2 rs3821204 C allele was higher in the HCC group than in the healthy control group; our results were consistent with the findings of Wei et al on Chinese HCC patients [ 46 ].…”
Section: Discussionmentioning
confidence: 99%